Real-time stability measurement system for postural control - Gopalai, Alpha; Senananayake, A.; Kiong, L.; Gouwanda, D. (Elsevier, 2011)
A method for assessing balance, which was sensitive to changes in the posturalcontrol system is presented. This paper describes the implementation of a force-sensing platform,with force sensing resistors as the sensing element. The platform is capable of measuringdestabilized postural perturbations in dynamic and static postural conditions. Besidesproviding real-time qualitative assessment, the platform quantifies the postural control ofthe subjects. This is done by evaluating the weighted center of applied pressure distributionover time. The objective of this research was to establish the feasibility of using the forcesensingplatform to test and gauge the postural control of individuals. Tests were conductedin Eye Open and Eye Close states on Flat Ground (static condition) and the balance trainer(dynamic condition). It was observed that the designed platform was able to gauge the swayexperienced by the body when subject’s states and conditions changed.